Measles Transmission in a Fully Vaccinated Closed Cohort: Data From a Nosocomial Clustered Cases in a Teenage Psychiatric Unit. Issue 9 (September 2019) - Hubiche, Thomas; Brazier, Camille; Vabret, Astrid; Reynaud, Sabrina; Roudiere, Laurent; del Giudice, Pascal
Abstract : We described nosocomially clustered cases of measles secondary to a nonvaccinated index case occurring in a teenage psychiatric unit despite optimum vaccine coverage. Surveillance of this fully vaccinated closed cohort showed a 7% attack rate. Vaccination limited the risk of complicated measles and the onset of a large outbreak.